Description of Neonatus Outcomes in Maternity Women with Preeclampsia and Gestational Hypertension at Regional General Hospital Tabanan - Ni Wayan Sriningsih; Ni Wayan Suarniti; Regina Tedjasulaksana (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Pregnancy hypertension is the highest cause of death in Indonesia. Worsening preeclampsia and gestational hypertension have impact on fetus. This study aims to determine outcome of neonates with preeclampsia and gestational hypertension at Tabanan Hospital during August 2022-2024. This research is descriptive with a crosssectional design. This study used total sampling with a sample size of 120 respondents. Secondary data was analyzed univariately, presented in frequency distribution table. Results showed characteristics majority of respondents were low risk age (79.2% preeclampsia, 85.4% gestational hypertension), multipara (68.1% preeclampsia, 70.8% gestational hypertension), pregnancy interval <10 years (50% preeclampsia, gestational hypertension 62.5%), preterm (54.2%) in preeclampsia and normal gestational age (75.0%) in gestational hypertension. Majority of preeclamptic neonates were vigorous babies (76.4%), LBW (55.56%) and normal body length (50%). Outcomes of gestational hypertension neonates were vigorous babies (91.7%), normal weight (79.2%) and normal body length (64.6%). Conclusions is majority were aged 20-35 years, multipara, pregnancy interval <10 years, preterm and normal gestational age (gestational hypertension). Majority of neonate outcomes were vigorous babies, LBW (preeclampsia), normal weight (gestational hypertension) and normal body length. The findings provide a basis for further research on Â outcomes of neonates from preeclampsia and gestational hypertension motherâ€™s.